Convection in a rectangular channel with a flow of water in laminar-turbulent transition with high heat fluxes - Silin, Nicolas; Masson, Viviana Patricia; Garcia, J. C. (Planta Piloto de Ingeniería Química, 2010)
Fil: Silin, Nicolas. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de Cuyo; Argentina. Comisión Nacional de Energía Atómica. Gerencia del Area de Energía Nuclear. Instituto Balseiro; Argentina